Ответы 1

  • yy=e^{kx}k^2*e^{kx}-6k*e^{kx}+9e^{kx}=0e^{kx}(k^2-6k+9)=0k^2-6k+9=0(k-3)^2=0Y=C_1e^{3x}+C_2xe^{3x} \left \{ {{C_1e^{3*0}+C_2*0*e^{3*0}=1} \atop {3C_1e^{3*0}+C_2e^{3*0}+3C_2*0*e^{3*0}=1}} ight.  \left \{ {{C_1=1} \atop {3C_1+C_2=1}} ight.  \left \{ {{C_1=1} \atop {3+C_2=1}} ight.  \left \{ {{C_1=1} \atop {C_2=-2}} ight. Y=e^{3x}-2xe^{3x}
    • Автор:

      annutb3
    • 5 лет назад
    • 0
  • Добавить свой ответ

Еще вопросы

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years